Application of large-diameter precise directional drilling borehole formation technology in coal mine construction - Zhang, Jinlong (Frontiers in Built Environment, 2025)
The application of large-diameter precise directional drilling for long boreholes demonstrates significant potential in coal mine construction, effectively overcoming the limitations of traditional drilling methods in long-distance crossings and complex geological formations. This study highlights the use of advanced directional guiding technologies, including triaxial accelerometers, magnetoresistance sensors, and intelligent trajectory control systems, to achieve precise borehole interconnections. In the Shangwan Coal Mine 22106 working face, large-diameter boreholes (120 mm, expanded to 203 mm) enhanced gas extraction efficiency, with average extraction concentrations reaching 80.2%, a 3.1-fold improvement compared to conventional methods (25.8%). The average gas extraction volume was 0.44 m3/min, representing a 10.3-fold increase over traditional techniques. Gas concentrations in roadways were maintained within a safe range of 0.27%–0.40%, enabling a monthly excavation progress of 400 m. A BP neural network model was employed for gas outflow prediction, achieving high accuracy with a deviation of less than 2% compared to field measurements. These findings demonstrate the transformative potential of this technology, ensuring safe, efficient, and rapid roadway construction in high-gas environments, with implications for broader applications in complex geological conditions.